Evaluating an intervention to improve belt fit for adult occupants. (February 2018) - Jones, Monica L.H.; Buckley, Lisa; Ebert, Sheila M.; Reed, Matthew P.; Hallman, Jason J.
Abstract: Introduction: Previous laboratory studies have demonstrated that some drivers position their seat belts suboptimally. Specifically, the lap portion of the belt may be higher and farther forward relative to the pelvis than best practice, and the shoulder portion of the belt may be outboard or inboard of mid-shoulder. This study evaluated the performance of a video-based intervention for improving the belt fit obtained by drivers. Method: Twenty-nine adult drivers participated in this study. Belt fit was measured before and after the intervention in participants' vehicles and in a laboratory mockup. Results: Data from both the in-vehicle and laboratory belt measures found that 95% of participants sampled improved some aspect of lap belt fit. For the in-vehicle test conditions, participants who lowered the lap belt location (Z) after the intervention showed an improvement of 26 mm on average. Among those participants who shifted the horizontal lap belt location rearward (closer to the pelvis), an average improvement of 36 mm was observed. No significant differences were observed between baseline and post-intervention shoulder belt fit. Conclusions: The results provide preliminary evidence that an intervention improves driver belt fit. More research is needed to establish what aspects of this intervention affected behavior and how effective such an intervention is in the context of public health. Practical applications: These findings can help better inform intervention initiatives to improve occupant belt fit. Highlights: Driver distraction appears in nearly 60% of the freeway rear-ending events extracted from the SHRP 2 NDS database. Causal model regarding driver distraction's impact on drivers' braking reaction time was explored. Distraction duration, distracted status when a leader braked, and secondary task type were associated with reaction time.